Significance of Single-Nucleotide Variants in Long Intergenic Non-protein Coding RNAs - Zou, Hecun; Wu, Lan-Xiang; Tan, Lihong; Shang, Fei-Fei; Zhou, Hong-Hao (Frontiers in Cell and Developmental Biology, 2020)
Single nucleotide variants (SNVs) are the most common genetic variants and universally present in the human genome. GWASs have identified a great number of disease or trait-associated variants, many of those are located in non-coding regions. Long intergenic non-protein coding RNAs (lincRNAs) are the major subtype of long non-coding RNAs, lincRNAs play crucial roles in various disorders and cellular models via multiple mechanisms. With rapid growth in the number of the identified lincRNAs and genetic variants, there is great demand for an investigation of SNVs in lincRNAs. Hence, in this article, we mainly summarize the significant role of SNVs within human lincRNA regions. Some pivotal variants may serve as risk factors for the development of various disorders, especially cancer. They may also act as important regulatory signatures involved in the modulation of lincRNAs in a tissue- or disorder-specific manner. An increasing number of researches indicate that lincRNA variants would potentially provide additional options for genetic testing and disease risk assessment in the personalized medicine era.